Gamification Effects on Motivation Quality and Self-Regulated Learning in EFL Vocabulary Study - Effendi Limbong (Journal of Innovation in English Education and Language Teaching, 2025)
Gamification has become a ubiquitous feature of digital vocabulary learning tools, yet evidence regarding its effects remains contested. Meta-analyses report modest positive effects on learning outcomes, but these averages obscure substantial heterogeneity in individual responses. Self-determination theory (SDT) distinguishes autonomous motivation (learning driven by interest and value) from controlled motivation (learning driven by external pressures or guilt). Gamification elements such as points, badges, and leaderboards may support basic psychological needs or undermine them, depending on implementation. This quasi-experimental study investigated (a) whether a gamified vocabulary app produced differential effects on autonomous versus controlled motivation compared with a non-gamified version matched for content, (b) whether observed differences in vocabulary learning outcomes were mediated by changes in motivation quality, and (c) whether self-regulated learning (SRL) behaviors were differentially affected by the intervention. A 10-week quasi-experiment assigned 127 Chinese EFL undergraduates to either a gamified condition (points, badges, levels, progress bars) or a non-gamified condition (content-identical, feature-matched, no game elements). Pre- and post-intervention measures included autonomous and controlled motivation for vocabulary learning (Academic Self-Regulation Questionnaire), SRL strategy use (Motivated Strategies for Learning Questionnaire), and vocabulary knowledge (receptive and productive tests). ANCOVA and mediation analyses were conducted. No main effect of condition on vocabulary gains emerged. However, the gamified group showed significantly higher controlled motivation at post-test (d = 0.52) and lower autonomous motivation (d = –0.38). Motivation quality fully mediated the gamification–vocabulary relationship: the gamified app indirectly harmed learning outcomes through increased controlled motivation, while the non-gamified app supported autonomous motivation. SRL strategy use declined in both groups, but gamification accelerated this decline for goal-setting and planning behaviors. Points and badges are not inherently motivating or demotivating. Their effects depend critically on whether they support autonomy or impose controlling pressures. EFL practitioners should exercise caution when implementing gamified vocabulary tools without attention to instructional framing that supports learners’ perceived autonomy and competence. Design principles for autonomy-supportive gamification are proposed.